The Virtual Enterprise – Citizen of the European Union - Andreea Davidescu (Vasile) (Romanian Journal of European Affairs, 2013)
The Virtual Enterprise is a rather young and unclear concept in the business world. A virtual enterprise is a temporary network of companies that share their different resources in order to reach a given goal (the creation of a new product, or the entry on a new market) and is a powerful tool in the hands of the business community. The question this article raises is whether European Union’s businesses are able to take advantage of this opportunity within the European Union. We discuss several obstacles towards the creation of virtual enterprises: regulatory uncertainties, operational management that dismisses the advantage of an excellent infrastructure, the orientation of innovation creators towards theoretical research and the European business culture. The article also looks at research on the virtual enterprise in the European Union, the legal framework and technologies for virtualization.